2016
DOI: 10.1089/jamp.2016.1291
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Aerosol Distribution in Human Airways: A Scintigraphy-Guided Study in a 3D Printed Model

Abstract: We showed combined imaging experiments and CFD simulations to systematically study aerosol deposition patterns in human airways down to generation 5, where particle deposition could be spatially linked to the airway geometry. As particles are negotiating an increasing number of airways in subsequent branching generations, CFD predicts marked deviations of aerosol distribution with respect to ventilation distribution, even in the normal human lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 30 publications
3
34
0
1
Order By: Relevance
“…Therefore, the human data reported here support the cast data as well as the computational fluid dynamics (CFD) simulations presented in Ref. (40) For scales smaller than the lobar level (segmental level), Verbanck et al reported a higher variability in the cast's ventilation-to-deposition ratio. The limited lung coverage and co-registration across modalities (limitations given next) limit our ability to produce reliable data at the scale of lung segments and sub-segments.…”
Section: Figsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, the human data reported here support the cast data as well as the computational fluid dynamics (CFD) simulations presented in Ref. (40) For scales smaller than the lobar level (segmental level), Verbanck et al reported a higher variability in the cast's ventilation-to-deposition ratio. The limited lung coverage and co-registration across modalities (limitations given next) limit our ability to produce reliable data at the scale of lung segments and sub-segments.…”
Section: Figsupporting
confidence: 89%
“…In a recent paper using a three-dimensional printed, realistic airway cast (mouth to generation 5), Verbanck et al (40) reported for 3 and 6 lm particles, at higher flows than the flow imposed here (30 and 60 L/min, compared with 15 L/ min), direct proportionality between lobar-level ventilation and aerosol distribution. The quartile lung regions used in our analysis samples ventilation and deposition across neighboring lobes.…”
Section: Figmentioning
confidence: 50%
“…Such altered flow patterns and aerosol deposition have been demonstrated using computational fluid dynamics in lung models. 39,40 Methods to reduce airway closure, such as application of positive expiratory pressure, may thus have benefit for improving inhaled drug deposition. 41 Our data reveal a median closing index of 0.67 among a large, diverse group of patients with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…As most asthma therapy is topically acting, the inhaler is of little use if it can only deliver a dose to the healthy part of the lungs while the diseased part goes untreated. 13 Therefore, the physical characteristics of the discharged aerosol dose are as vital for a successful outcome as the pharmacodynamics of the drug itself. Particle size is the most important physical property of the aerosol cloud and is an important determinate of how far into the airways a dose can be delivered.…”
Section: Desirable Inhaler Characteristics For Treating Asthmamentioning
confidence: 99%